Effects of methyl mercury on the activity and gene expression of mouse Langerhans islets and glucose metabolism. (July 2016) - Maqbool, Faheem; Bahadar, Haji; Niaz, Kamal; Baeeri, Maryam; Rahimifard, Mahban; Navaei-Nigjeh, Mona; Ghasemi-Niri, Seyedeh Farnaz; Abdollahi, Mohammad
Abstract: Mercury (Hg) is a well-known heavy metal and causes various toxic effects. It is abundantly present in fish in the form of methyl mercury (MeHg). Also, various other forms of mercury can enter human body either from environment like inhalation or through dental amalgams. The present study was designed to assess MeHg induced toxicity in mouse plasma and pancreatic islets with respect to insulin secretion, oxidative balance, glucose tolerance, gene expression, caspases 3 and 9 activities. MeHg was dissolved in tap water and administered at doses 2.5, 5 and 10 mg/kg/day, for 4 weeks. In mice, MeHg significantly caused increase in plasma insulin as well as C-peptides. Glucose intolerance, insulin resistance and hyperglycemia are main consequences of our study that correlate with the gene expression changes of glucose homeostasis as well. MeHg caused increase lipid peroxidation in a dose-dependent manner in plasma as well as pancreatic islets. In addition, total thiol molecules and ferrous reducing antioxidant power in MeHg treated group was decreased in plasma as well as pancreatic islets. Caspases 3 and 9 activities of pancreatic islets were upregulated in MeHg exposed animals. Reactive oxygen species were extremely high in pancreatic islets of MeHg treated groups. MeHg disrupted gluconeogenesis/glycogenolysis pathways and insulin secretory functions of islets by targeting GDH, GLUT2 and GCK genes of pancreatic islets. In conclusion, the current study revealed that insulin pathways, oxidative balance and glucose metabolism encoded genetic makeup are susceptible to MeHg toxicity and the subsequent oxidative stress and alternations in gene expression could lead toward functional abnormalities in other organs. Graphical abstract: A schematic view of MeHg induced insulin resistance and diabetes through oxidative impairment in plasma. LPO: Lipid peroxidation. FRAP: Ferrous reducing antioxidant power. ROS: Reactive oxygen species. OGTT: Oral glucose tolerance test. Highlights: Glucose intolerance and high fasting blood glucose was induced by methyl mercury (MeHg). MeHg caused hyperinsulinemia in plasma and ultimately triggered insulin resistance. MeHg disrupted gluconeogenesis and insulin secretory functions of islets through targeting GDH, GLUT2 and GCK genes. MeHg induced oxidative stress and triggered Caspases 3 and 9 activities in the islets.